All Days 2012
DOI: 10.2118/160848-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of Low Permeability Reservoir Utilizing Multi-stage Fracture Completion in the Minimum Stress Direction

Abstract: Saudi Aramco is developing several gas fields in the Eastern Province of Saudi Arabia by drilling horizontal wells in the Khuff and pre-Khuff tight carbonate and sandstone formations. To date, many wells have been drilled in the maximum horizontal stress direction with virtually no wellbore instability occurring during the drilling operation. When these wells are hydraulically fractured, the fracture grows along the wellbore in the direction of well azimuth. To avoid overlapping of two adjacent induced fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Recently published papers (Rahim et al 2011;Ahmed et al 2012;Rahim et al 2013) suggested that drilling in min with multistage fracturing (MSF) operations provides better production results in tighter reservoirs due to the increased reservoir contact obtained from transverse fractures compared to the longitudinal ones. A properly designed and executed P&P technique provides even more benefits as it allows propagation of multiple fractures in a single stage, thereby further increasing the reservoir contact area.…”
Section: Technology Descriptionmentioning
confidence: 99%
“…Recently published papers (Rahim et al 2011;Ahmed et al 2012;Rahim et al 2013) suggested that drilling in min with multistage fracturing (MSF) operations provides better production results in tighter reservoirs due to the increased reservoir contact obtained from transverse fractures compared to the longitudinal ones. A properly designed and executed P&P technique provides even more benefits as it allows propagation of multiple fractures in a single stage, thereby further increasing the reservoir contact area.…”
Section: Technology Descriptionmentioning
confidence: 99%
“…Appendix A provides confirmation that a similar trend exists with most of the productivity parameters. Previously published papers (Rahim et al 2011;Ahmed et al 2012;Rahim et al 2013) came to a similar conclusion that drilling in the min direction for MSF operations provides better production results in the carbonate reservoir. But some exceptions from the trend can be seen for wells H2 and H7.…”
Section: Well Azimuth (Horizontal Wells Only)mentioning
confidence: 71%
“…This fracturing technique is suitable for very low to moderate permeability reservoirs, where long, single induced fractures are needed to enhance well productivity. [7][8][9][10] In LEMA, multiple nozzles are placed in a single interval to create strong matrix acidizing effect throughout the entire open-hole interval. The nozzles are adjusted and placed to suit different reservoir characteristics for optimum treatment.…”
Section: Description and Function Of Limited Entry Ohms System (Lema)mentioning
confidence: 99%